Methodology investigation: Impact of crown geometry, crown, abutment and antagonist material and thermal loading on the two-body wear of dental materials. Issue 2 (February 2022) - Schmeiser, Felix; Arbogast, Fee; Ruppel, Hendrik; Mayinger, Felicitas; Reymus, Marcel; Stawarczyk, Bogna
Abstract: Objectives: To investigate the impact of crown geometry, crown/abutment/antagonist material and thermal loading on the two-body wear of dental materials caused by chewing simulation. Materials and methods: For the crown geometry, crowns (polymethylmethacrylate (PMMA), polyetheretherketone (PEEK) and silicate ceramic (SiO2 )) were milled with a flat, steep, or medium cusp inclination (CINC). For the crown/abutment material, crowns (PMMA, PEEK and SiO2 ) were combined with PMMA, polymer-infiltrated-ceramic-network (PICN), cobalt-chrome alloy (CoCr) and natural teeth (ENAM) abutments. For the antagonist material, antagonists were fabricated from PICN, CAD/CAM resin composite (RECO), steatite (STEA), steel (STL) and ENAM and tested against flat specimens (substrates) made of veneering ceramic (VC). For thermal loading, the duration (30 s, 60 s, 120 s) and presence of temperature changes (37 °C versus 5 °C/55 °C) was varied. Material losses were determined by matching scanned specimens before and after aging (400, 000 chewing cycles, 50 N, 1.3 Hz). Martens parameters were determined for the antagonists/substrates. Data were analyzed using Kolmogorov-Smirnov-test, Kruskal-Wallis H, Scheffé-Post-Hoc-tests, pairwise comparisons, Bonferroni correction, one-way ANOVA, Mann-Whitney-U and Spearman rho. Results: PMMA crowns presented the highest and PEEK the lowest material losses. Flat CINC showed the lowest material losses for PEEK and SiO2 crowns. CoCr and ENAM abutments presented material losses in the same range. Antagonist and cumulative material losses for RECO and ENAM were similar. Thermal loading did not influence material losses. Significance: Crown geometry influences the crown and antagonists wear, with an increased cusp inclination entailing increased wear. For in vitro set-ups, CoCr abutments and RECO antagonists present valid alternatives to natural teeth. For polymers, in vitro chewing simulations may be performed at a constant temperature (37 °C).